Beyond munificence: Economic thinking and financial transactions in Roman aphrodisias - Eugenia Vitello (The Journal of European Economic History (JEEH), 2024)
During the Hadrianic period (117-138 CE), Attalos Adrastos of Aphrodisias left two generous endowments to fund civic and reli- gious services. Although private donations are common means of civic up-keeping, at a closer look Adrastos employed financial de- vices that allowed him to profit from his own gifts both in terms of social and economic assets. The present paper will present Adras- tos' benefactions as exemplar of the donors' financial behaviour, uncovering their personal economic interests lying behind appar- ently selfless euergetic acts. Through a careful re-reading of the in- scriptions in their historic context, I will prove that ancient donations were not conceived as means of spreading wealth more equally within the urban fabric, but rather of accumulating material and im- material capital more firmly in the hands of the benefactors and their kins by creatively employing conscious investment-schemes to minimize the expenses while maximizing the profits.
Keywords: 330